USING DIGITAL TECHNOLOGIES IN THE TRAINING PROCESS OF VOLLEYBALL PLAYERS - Kamola Muradova (Bright Mind Publishing, 2025)
This article explores the application of digital technologies in the training process of volleyball players in Uzbekistan. With the increasing global integration of sports and technology, digital tools such as motion analysis systems, wearable trackers, smart sensors, and video analytics have transformed the way athletes train and perform. The study examines how these technologies contribute to improving the physical preparedness, technical-tactical performance, and injury prevention among volleyball players. The research also considers the current availability, implementation challenges, and effectiveness of these tools within the Uzbek sports context, particularly in volleyball clubs and educational institutions. The findings underscore the importance of digital integration for modern training systems and propose recommendations for optimizing technology use in sports education.
Keywords: Volleyball, digital technologies, sports training, video analysis, wearable devices, smart sensors, Uzbekistan, athlete performance, injury prevention, training optimization.